Evaluación del desempeño de un lodo de perforación base aceite a escala de laboratorio implementando arcilla organofílica modificada (2021)
In the present work, the performance of an organophilic clay in two types of oil-based mud (OBM) was evaluated by modifying a bentonite clay with two types of quaternary ammoniums, since clays of the montmorillonite type, originally hydrophilic when treated with ammonium salts quaternary are transformed into organophilic, which allows them to produce thixotropic, viscous and gelling phenomena in different fields of industry. The organophilic clay was synthesized by a method in which a dispersion of deionized water is made together with the bentonite and later the quaternary ammonium (benzalkonium chloride, fifth generation quaternary ammonium) is added, which allows ion exchange.